The influence of cytoreductive surgery on survival and morbidity in stage IVB endometrial cancer. Issue 5 (1st August 2002) - Ayhan, A.; Taskiran, C.; Celik, C.; Yuce, K.; Kucukali, T.
Abstract : The purpose of this study was to detect possible survival advantages of surgical cytoreduction and different adjuvant treatment regimens for stage IVB endometrial cancer patients, and also to evaluate the prognostic importance of surgico-pathological risk factors and surgical morbidity rates. Thirty-seven FIGO stage IVB endometrial cancer patients treated at the Hacettepe University Hospital between 1977 and 1998 were included in this study. Clinical data were obtained from the private oncology files and all specimens were re-evaluated by the co-author pathologist. Optimal cytoreduction was defined as a surgical procedure leaving the patient with ≤1 cm residual disease in maximal diameter. All patients were subjected to initial cytoreductive surgery, but it had been achieved for 22 (60%) patients. Fourteen (38%) patients received both radiotherapy and chemotherapy, 10 (27%) patients received only radiotherapy and the other 10 (27%) patients received only chemotherapy. Three patients refused any type of adjuvant therapy. The median survival of the suboptimally cytoreduced patients was 10 months, while the median survival in the optimal group was 25 months ( P = 0.001). In optimal cytoreduction group, the median survival for 12 (55%) patients without visible tumor was 48 months compared to 13 months in 10 (45%) patients with visible tumor. As an adjuvant treatment, concomitant cisplatin and radiotherapy revealed 54 months median survival compared to 15 and 13 months in patients treated with only radiotherapy and only chemotherapy, respectively. By univariate analysis, extra-abdominal metastases, suboptimal cytoreduction, visible tumoral mass after cytoreduction, pelvic-para-aortic lymphatic metastases, and cervical invasion were found to be significant predictors of poor survival. In multivariate analysis, optimal cytoreduction, concomitant cisplatin-radiotherapy treatment, and extra-abdominal metastases were significant. Morbidity was mild in six (16%), and severe in nine (24%) patients. We conclude that optimal cytoreduction achieved significant survival benefit for stage IVB endometrial cancer patients with a reasonable surgical morbidity rate. As an adjuvant treatment, concomitant cisplatin and radiotherapy was the best choice.